Insights into monkeypox pathophysiology, global prevalence, clinical manifestation and treatments - Niu, Liyan; Liang, Dingfa; Ling, Qin; Zhang, Jing; Li, Ziwen; Zhang, Deju; Xia, Panpan; Zhu, Zicheng; Lin, Jitao; Shi, Ao; Ma, Jianyong; Yu, Peng; et al. (Frontiers in Immunology, 2023)
On 23rd July 2022, the World Health Organization (WHO) recognized the ongoing monkeypox outbreak as a public medical crisis. Monkeypox virus (MPV), the etiological agent of monkeypox, is a zoonotic, linear, double-stranded DNA virus. In 1970, the Democratic Republic of the Congo reported the first case of MPV infection. Human-to-human transmission can happen through sexual contact, inhaled droplets, or skin-to-skin contact. Once inoculated, the viruses multiply rapidly and spread into the bloodstream to cause viremia, which then affect multiple organs, including the skin, gastrointestinal tract, genitals, lungs, and liver. By September 9, 2022, more than 57,000 cases had been reported in 103 locations, especially in Europe and the United States. Infected patients are characterized by physical symptoms such as red rash, fatigue, backache, muscle aches, headache, and fever. A variety of medical strategies are available for orthopoxviruses, including monkeypox. Monkeypox prevention following the smallpox vaccine has shown up to 85% efficacy, and several antiviral drugs, such as Cidofovir and Brincidofovir, may slow the viral spread. In this article, we review the origin, pathophysiology, global epidemiology, clinical manifestation, and possible treatments of MPV to prevent the propagation of the virus and provide cues to generate specific drugs.